Helping Students Create Their Own Books the Dialogic Way - Jacobs, George (Beyond Words, 2020)
This article explores one technique that is consistent with the student-centered paradigm in language education: student-generated books. First, benefits of student-generated are dis-cussed. Then, the article explores the crucial area of maintaining student ownership of their own books. The next topic explained in the article is why dialog is important as the students are developing their books. Finally, it is suggested that book creation works for students of all ages and levels, with examples given of students at the early childhood level and of second language students at university level.